2023 China and global food policy report: Promoting sustainable healthy diets for transforming agrifood systems - China Agricultural University; Zhejiang University; Chinese Center for Disease Control and Prevention; Nanjing Agricultural University; International Food Policy Research Institute; Food and Land Use Coalition; World Resources Institute (2023)
The current situation of global food and nutrition security is increasingly worrisome, and it is unfortunate that progress in eliminating hunger, food insecurity, and multiple forms of malnutrition has been hindered or even reversed by recent global events. It is estimated that globally, 702 million to 828 million people (8.9 to 10.5 percent) suffered from hunger in 2021, with 150 million added during the COVID-19 pandemic. Approximately 2.3 billion people are in a state of moderate or severe food insecurity, with 11.7 percent facing severe food insecurity. Nearly 3.1 billion people could not afford a healthy diet, which is an increase of 112 million from the last year. The causes of food insecurity are multifaceted, including the impact of the COVID-19 pandemic, the crisis in Ukraine,and climate change. Simultaneously, income levels have been adversely affected, and prices have risen, reducing people’s ability to purchase food and making it unaffordable. Therefore, it is imperative for governments and other stakeholders to act collectively to improve the state of global food and nutritional health. Many countries, including China, have begun to pay more attention to the issue of agrifood systems and are proposing a transition to the multidimensional goals of nutrition and health, green and low-carbon, efficiency, resilience, and inclusiveness. At the international level, a series of high-level international conferences and action plans, such as the UN Food Systems Summit, the Nutrition for Growth Summit, and UN Climate Change Conference (COP26) in 2021 and COP27 in 2022, have demonstrated the importance and urgency of promoting the transformation of agrifood systems. These conferences advocated for countries to work together to transform the way food is produced and consumed to build healthier, sustainable, and equitable food systems. At the domestic level, China has always regarded food security as a top priority for national development. In 2022, the total annual national grain output reached 686.53 million tons and has remained stable for eight consecutive years at more than 650 million tons. In 2022, the Chinese government emphasized the need to “establish a big food concept” and “strengthen the foundation of food security in all aspects” from the perspective of putting people first and better meeting their increasingly diversified food consumption needs. In light of the various risks and challenges posed by the contemporary era, safeguarding food security necessitates a shift from a narrow focus on food production to a more comprehensive consideration of the entire food supply chain. This entails promoting the development of a diversified food supply system and expanding the focus from mere quantity to encompassing multiple objectives related to the “quantity, structure, and quality” of food. Such an approach will serve to bolster the foundations of food security on all fronts.